Vertical position can affect categorization of the rich and the poor in Chinese culture. (June 2021) - Li, Qiong; Deng, Chen; Zuo, Bin; Zhang, Xiaobin
This study explored whether vertical position affects social categorization of the rich and the poor. Experiment 1 used high- and low-income occupations as stimuli, and found participants categorized high-income occupations faster when they were presented in the top vertical position compared to the bottom vertical position. In Experiment 2, participants responded using either the "up" or "down" key to categorize high- and low-income occupations, and responded faster to high-income occupations with the "up" key and low-income occupations with the "down" key. In Experiment 3, names identified as belonging to either rich or poor individuals were presented at the top or bottom of a screen, and the results were the same as in Experiments 1 and 2. These findings suggest that social categorization based on wealth involved perceptual simulations of vertical position, and that vertical position affects the social categorization of the rich and the poor.